Prognostic value of pretreatment C-reactive protein/albumin ratio in nasopharyngeal carcinoma: A meta-analysis of published literature. Issue 30 (July 2018) - Yang, Xiaodi; Liu, Hongjian; He, Minfu; Liu, Meitian; Zhou, Ge; Gong, Ping; Ma, Juan; Wang, Qi; Xiong, Wenjing; Ren, Zheng; Li, Xuanxuan; Zhang, Xiumin
Abstract: Background: To explore the prognostic value of C-reactive protein/albumin ratio (CAR) in nasopharyngeal carcinoma (NPC), we conducted a comprehensive meta-analysis of relevant literature on the association between CAR and NPC outcome. In recent years, an increasing number of studies has been published analyzing the possible prognostic utility of C-reactive protein/albumin ratio (CAR) in nasopharyngeal carcinoma (NPC), but the results are still controversial. Methods: A relevant literature search was performed by using the PubMed, Embase, Web of Science, Cochrane Library, CBM, Wanfang, VIP, and China National Knowledge Infrastructure databases to evaluate the prognostic value of CAR in patients with NPC. The last date of our primary search was December 5, 2017. This meta-analysis was conducted on the basis of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Pooled hazard ratio (HR) with 95% confidence interval (95% CI) was utilized to estimate the association of CAR and overall survival (OS) and distant metastasis-free survival (DMFS). Results: Five studies that enrolled 5533 patients with NPC were finally quantified. Our findings revealed that high pretreatment CAR was significantly associated with poor OS (HR = 1.58, 95% CI = 1.36–1.83, P < .001) and DMFS (HR = 1.25, 95% CI = 1.09–1.44, P = .002). The findings from most subgroup meta-analyses were in line with those from the overall meta-analyses. No significant heterogeneity was observed among the included studies for OS and DMFS ( P > .05); however, publication bias was found for OS ( P < .05). Conclusion: Our meta-analysis suggests that high pretreatment CAR indicates poor prognosis in NPC. Thus, pretreatment CAR serves as a prognostic marker in NPC and can be used to evaluate prognosis in clinical work.